Curriculum Management In Improving The Quality Of Education - A’an Yusuf Khunaifi; Ganang Setyo Herlambang; Ahmad Sodikin (International Journal of Advanced Studies in Educational Management (IJASEM), 2025)
This study aims to explain student management in improving student discipline in MTsN 1 Kediri.  The research method used is descriptive qualitative. Data were taken using interviews, observations, and documentation studies. In this study, the subjects of the study were the principal, the vice principal for curriculum and student affairs, and several students and teachers. The results of this study show that: First, MTsN 1 Kediri plans several activities to shape student discipline. Second, the implementation of some of these programs is proceeding in an orderly manner according to the schedule plan. Third, evaluation of the implementation of student activities is carried out once a semester which is conducive. discusses the ups and downs of student achievement stability and discipline in MTsN 1 Kediri